1996
DOI: 10.1007/bf00312095
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous mastitis diagnosed and followed up by fine-needle aspiration cytology, and successfully treated by corticosteroid therapy: Report of a case

Abstract: A 36-year-old woman presented to our hospital with a rapidly growing lump in her left breast. Fine-needle aspiration (FNA) cytology of the mass revealed many epithelioid cells admixed with multinucleated Langhans-type giant cells, neutrophils, lymphocytes, and stromal cells, leading to a diagnosis of granulomatous mastitis. This report describes the clinical course of this patient in whom granulomatous mastitis was successfully treated with corticosteroid therapy. Special reference is made to the usefulness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 4 publications
0
50
0
Order By: Relevance
“…One third of the patients with granulomatous mastitis have a history of oral contraceptive use in some publications (7). Two (17%) of our cases were on oral contraceptives at the time of diagnosis (4,8,22,(25)(26)(27). The infectious agents were implicated in the etiology of GLM, but they have not been isolated and proven so far (9).…”
Section: Figure 2 Mammographic Imaging Of the Breast Before Treatmenmentioning
confidence: 80%
See 1 more Smart Citation
“…One third of the patients with granulomatous mastitis have a history of oral contraceptive use in some publications (7). Two (17%) of our cases were on oral contraceptives at the time of diagnosis (4,8,22,(25)(26)(27). The infectious agents were implicated in the etiology of GLM, but they have not been isolated and proven so far (9).…”
Section: Figure 2 Mammographic Imaging Of the Breast Before Treatmenmentioning
confidence: 80%
“…We believe the steroid regimen has the advantage of a low rate of side effects. Despite GLM has no optimal management, there are publications of recent studies reporting that large surgical excision following or without a steroid therapy is a favorable treatment of choice (2,9,23,26,27,41). Asoglu et al (23) reported that, among 18 cases who had undergone large local excision, recurrence was observed only in one case during 36 months of follow-up, who was treated with re-excision.…”
Section: Figure 2 Mammographic Imaging Of the Breast Before Treatmenmentioning
confidence: 99%
“…Although wide excision of the mass was traditionally performed in the past, this was followed by a high rate of recurrence, skin ulceration, abscess formation, fistulae formation, and wound infection [1,4,9]. Corticosteroid therapy is effective in decreasing the granulomatous mass in this disease [4,10,11]. Many of the previous reports on IGM have focused on the histological and radiological features; however, few reports have been published on the progress of this disease when treated with corticosteroids [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Medical treatment with corticosteroids provides significant regression of the inflammatory disease allowing more conservative surgery. 12 Consecutive surgical excision of the remaining lesions with good cosmetic results provides definitive treatment and reduces the risk of recurrence. 8,11 …”
Section: Resultsmentioning
confidence: 99%